P007 Effective clinical designs of multiplex point-of-care-tests for genital discharge syndrome management in women: which pathogen combinations and testing protocols deliver the best outcomes?. (8th June 2017) - Kolodziejczyk, Anna; Broad, Claire; Harrison, Mark; Fuller, Sebastian; Okala, Sandra; Harding-Esch, Emma; Sadiq, STariq
Abstract : Introduction: Syndromic management of sexually transmitted infections (STIs) is common practice in sexual health clinics (SHC). Implementation of multi-pathogen point-of-care-tests (POCTs) can improve patient management by providing same day diagnoses and treatment. We assessed the potential impact of five POCT protocols consisting of tests for different combinations of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG) and Trichomonas vaginalis (TV) infections, on a standard care pathway (SCP), for 81 symptomatic female patients. Methods: 5 virtual POCT protocols (assuming 100% sensitivity and specificity) were analysed against diagnoses and laboratory results. Reflex tests (i.e. tests used dependent on the result of another test) were incorporated into protocols to investigate utility of testing for certain pathogens separately. McNemar's test was used to compare proportions of correct diagnoses from each protocol against each other and establish which is most effective. P values were adjusted using Holm-Bonferroni correction. Results: Protocol P1 was statistically the most effective at providing the correct diagnosis (p=0.000). P5 was also statistically more effective than the SCP (p=0.001). No significant differences were found between other protocols. Although P4 and P5 diagnosed equal proportions of patients, P5 had better performance (p=0.001) compared with P4 (p=0.0012). Discussion: P1 was more effective than the SCP and all other protocols, however, may not be technically feasible. P5 was not statistically different from P1 and may be a valid alternative. Due to high rates of MG and CT infection in this cohort, a protocol including tests for both pathogens would be desirable for this population.